PELAKSANAAN KOORDINASI PENERTIBAN PENDERITA GANGGUAN JIWA STUDI KOOPERATIF DINAS SOSIAL DAN PEMAKAMAN DENGAN SATUAN POLISI PAMONG PRAJA KOTA PEKANBARU - Betty Febtia Tauri; Ahmad Tarmizi Yussa (UIR Press, 2018)
This study aims to determine the objective level Implementation Coordination Control of Patients with Mental Disorders Cooperative Study of Dinas Sosial and Pemakaman with Satuan Polisi Pamong Praja Pekanbaru Ciy]ty . Indicators used include the coordination of research policies, plans , procedures and work , meetings and briefings , and a joint decree .This type of research is mrnggunakan tenik Diskriptif Survay data collection such as interviews , questionnaires , and document review , and analyze the data that has been prepared on the object of research and comparing with the theory related to the problem . Then analyzed qualitatively and quantitatively for comparing reality with references that have to do with the analysis related to research in the form of concise and clear description perpetually . the location was used in tfis study is the Dinas Sosial and Pemakaman with satuan Polisi Pamong Praja Pekanbaru city.Based on this analysis technique that implements selected research concludes Coordination of Dinas Sosial and Pekakaman with Satuan Polisi Pamong Praja Pekanbaru City is in the interval Good Enough . This Kesimplan accordance with the measurement technique that has been set that is done categories Good Enough is of five indicators used have not all done well.